Dimensions of Strategic Quality Management and Its Role in Achieving the Requirements of Green Manufacturing: Analytical Study of The Opinions of a Sample of Managers in a Number of Industrial Companies for the Production of Mineral Water in Dohuk Governate - Gulli, Mehvan; Ahmed, Zaravan (Humanities Journal of University of Zakho, 2021)
This study aims to determine the role of the strategic quality management dimensions in achieving the requirements of green manufacturing, the sector of the industrial companies was identified as a field for conducting the practical side. The study included (96) individuals working in the researched companies, and the data were collected by relying on the questionnaire form prepared for this purpose. the data were analyzed using a set of statistical methods in the (SPSS V.24) program to analyze the correlation and regression relationship between the study variables. The outcome of the research was that a number of conclusions were reached. The most important of which is the existence of a positive moral correlation between the dimensions of strategic quality management and green manufacturing, as well as the presence of a significant impact of the dimensions of strategic quality management in green manufacturing. The need for the researched companies to work to enhance and maintain high levels of senior management commitment to quality due to its great role in supporting and implementing the strategic quality management of these companies, because the researched companies cannot provide products of strategic quality to their customers without the commitment of the top management in them.